On the issue of high school students’ emotional intelligence development by psychology-pedagogical means - Mohilyasta , Svitlana (Psychological Prospects Journal, 2020)
Purpose. Сonsidering emotional intelligence as an integral part of the individual’s basic characteristics , today there is an important problem of psychological and pedagogical science and a main task of searching ways for developing it. The purpose of the article is to consider theoretical approaches in the field of searching psychological and pedagogical means for developing emotional intelligence and the possibilities which English lessons give as ways of high school students’ emotional intelligence formation, functioning and development. Methods. There are theoretical and empirical research methods on the development of high school students’ emotional intelligence and experimental implementation into the process of learning English elements of psychological exercises. Considering the process of developing emotional intelligence in terms of ontogenetic changes in the ability to understand and manage emotions and feelings; purposeful influence on the individual components of emotional intelligence development; there is a relevant problem of searching ways to develop high school students’emotional intelligence. Educational process, and the integration of psychological exercises elements into the process of studying a subject such as English. Results. It is represented a theoretical analysis of the conceptual foundations of the problem determining a thesaurus «means of development». The practical application of the suggestopedia elements into a contemporary lesson of English, in the direction of developing skills recognizing, verbalizing, managing emotions and in accordance with the topics of situational communication provided by the State Program for Teaching Foreign Languages. Conclusions. The range of psychological exercises possibilities and methods in combination with linguo-didactic content there is partially considered and detailed in terms of a contemporary lesson of English. It is created a generalization, which substantiates the need for a continuum in the direction of creating the system for high school students’ emotional intelligence developing by psychological and pedagogical means within the space of the educational institution, basised on detailed theoretical and methodological concept it is considered promising.
Keywords: emotional intelligence; means of development; art; high school students; English lesson